The Effect of Integrated Governace, Risk and Compliance (GRC) on Firm Value Through Finacial Performance (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to test and analyze the effect of GRC and Intellectual Capital on firm value through financial performance in banking companies. The population in this study are all banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Sampling using purposive sampling method. The data used is secondary data sourced from annual reports and financial reports. The data analysis technique used in this research is the SmartPLS 4 program. The results of this study indicate that GRC has no significant effect on financial performance and firm value, Intellectual capital has no effect on firm value but intellectual capital has a significant and positive effect on financial performance. Furthermore, financial performance has no influence on firm value. GRC mediated by financial performance has no effect on firm value. Intellectual Capital mediated by financial performance has no effect on firm value.